Decision Making Techniques For Selecting Female Dormitory Supervisors Using The Technique Method For Others Reference By Similarity To Ideal Solution - Billy Siallagan; Vanessa Leisa sitanggang; Novita Limbong; Rony sidabariba (Sean Institute, 2024)
The female student dormitory at Santo Thomas Catholic University Medan serves as a temporary residence for female students who come from outside Medan. Dormitory supervisors play an important role in the management and supervision of the dormitory, ensuring the safety and well-being of residents. However, the selection of new coaches faces obstacles, such as lack of qualifications and potential conflicts of interest. To address these issues, this research applies the Technique for Order Preference by Similarity to Ideal (TOPSIS) method as a decision-making tool. This method allows the comparison of alternatives to prospective coaches based on set criteria. The results show that the TOPSIS method is effective in determining suitable candidates for female dormitory coaches, thus supporting the establishment of a safe and supportive environment for female students. This research emphasises the importance of a transparent selection process and oversight mechanism to prevent conflicts and ensure the integrity of the candidate.